An analysis of responses on Twitter to the English Premier League's support for the anti-homophobia rainbow laces campaign. Issue 2 (1st February 2023) - Hansen, Matilda; Kavanagh, Emma; Anderson, Eric; Parry, Keith; Cleland, Jamie
Abstract: This article examines the responses by users of the social media platform, Twitter, to the English Premier League's (EPL) support, via four tweets from their official Twitter account, for the annual Rainbow Laces anti-homophobia in football campaign. Locating our analysis within the corporate social responsibility (CSR) agenda of the EPL, the four tweets received a total of 24, 997 'likes', 4, 951 retweets, and 1, 865 comments. Of those comments directly responding to the campaign and wider CSR agenda of the EPL (n = 407), 236 contained supportive comments and 171 contained negative comments. Despite support for the Rainbow Laces campaign, the comments also reflected some resistance to the overall CSR agenda of the EPL. Here, responses called for a greater focus on issues outside of LGBT+, such as mental health and reducing the financial burden placed on fans to consume football.